(3aGcgI GdNdaGA hoeaGcgIGdoXQaGAs - (3CMeO Hf eMeO Hf YHO Gddg Hf EHQGgje, CHh eMeO, TgGH GdOjf, GdeYQha HGHf nYnQrHTGg , J (B854 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf Gddg GdebOS aj PGJg bO ChOY aj cd PQI ef eNdhbGJg s
(3BNQgG (B:s
(3hdabg eUfag ef ZjQ JQOO hdG JacQ eY JhRY GdHGd s
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3fSNI KGfjIs
(3HChdgG agQS ddehVhYGJs
(3hHgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B122s
Keywords: (3GdCOHs